Two Novel Grey System Models and Their Applications on Landslide Forecasting - De-Yi Ma; Jian-Lin Li (Journal of Control Science and Engineering)
For the small sample poor information, grey model is one of the good forecasting models. However, the simulation curve of original data is not consistent with that of the data by translations. In this paper, we present two novel grey system models, that is, generalized grey model and generalized discrete grey model. Compared with grey model, we prove that the simulation curve of original data is consistent with that of the new data by translations for the novel grey model, which was also demonstrated by the results of practical numerical examples.